Compaction and pore-collapse of chalky limestones from Mururoa atoll - Aubry, Jérôme; Bollinger, Laurent; Schubnel, Alexandre; Deldicque, Damien; Fortin, Jérôme (Comptes Rendus. Géoscience)
Between 1975 and 1996, the Centre d’Expérimentation du Pacifique (CEP) carried out French underground nuclear tests under the atoll of Mururoa (French Polynesia). The deformation of its coral rim was extensively monitored in order to assess the stability of the outer slopes, in particular since a flank collapsed in 1979, triggering a landslide-generated tsunami. The atoll has attracted the attention of experts since the beginning of the nuclear tests because of the mechanical behavior of porous and weak chalky limestones at depth. In this study, samples of these rocks, which were extracted from the atoll’s rim through drilling, have been deformed in the laboratory. The implications of the experiments provide a new perspective on the deformation of the Mururoa atoll since the end of nuclear tests—and, by extension, on the micromechanics of chalks for several other geological contexts.